GE_GERICHTE P/11885/2011 vom 18. Oktober 2019 - GE Cour de justice (2019)
CONFRONTATION;PRINCIPE DE L'ACCUSATION;MEURTRE;TENTATIVE(DROIT PÉNAL);COMPLICITÉ;LÉSION CORPORELLE GRAVE;LÉSION CORPORELLE SIMPLE;PRINCIPE DE LA CÉLÉRITÉ;MESURE DE SUBSTITUTION À LA DÉTENTION | CP.111; CP.122; CP.129; CP.123; CP.22; CP.25; CP.51; CPP.9; CPP.147; CPP.5.al1